Epistemic Injustice or Epistemic Oppression? - Catala, Amandine (KULA)

(untitled) (University of Victoria Libraries, 2024)
The concepts of epistemic injustice and epistemic oppression both aim to track obstacles to epistemic agencyーi.e., forms of epistemic exclusionーthat are undue and persistent. Indeed, the two terms are often used interchangeably. In this paper, I begin by addressing the question of whether the concepts of epistemic injustice and of epistemic oppression are in fact synonymous, and how we might articulate the relation between the two. I argue that while they partly overlap, the two concepts are not synonymous, and that one fruitful way to characterize their relation is by drawing on the distinction between systematic and incidental epistemic injustice. I then turn to the question of what might be gained or lost by focusing on one concept rather than the other. I argue that the concept of epistemic injustice, specifically that of incidental epistemic injustice, allows us to track certain types of undue and persistent obstacles to epistemic agency that the concept of epistemic oppression does not, but that should nonetheless be of interest to theorists of epistemic oppression. I close with some suggestions for further avenues to explore in order to gain a richer and more precise understanding of the various forms that problematic epistemic exclusion can take and how we might characterize them within our philosophical taxonomies.